Are abundant natural resources in the Democratic Republic of the Congo a blessing or curse? - Olamilekan Abdulwahab, Lawal; Arvian Firmansyah , Egi (Journal of Innovation in Business and Economics, 2024)
This study investigates how natural resources and institutional quality (IQ) impact the economic growth of the Democratic Republic of the Congo (DRC). Based on data annually from 1985 to 2022 using ordinary least squares regression the findings highlight that human capital development, inflation, foreign direct investment (FDI), oil rents, forest rents, political instability, conflict, and corruption significantly hinder the country's economic progress. This suggests that despite its abundant natural resources, the DRC faces more economic challenges than benefits from them. As a result, the study recommends stringent monitoring and oversight of mineral revenue management, establishment of stable political conditions, and aggressive measures to combat corruption and conflict. These actions are crucial in transforming the current curse of natural resources into a potential blessing for the country.